2007
DOI: 10.1017/s1041610207004978
|View full text |Cite
|
Sign up to set email alerts
|

Panic disorder in later life: results from a national survey of Canadians

Abstract: Background: At present, our understanding of the risk markers associated with panic disorder among older, community dwelling older adults is limited. To address this gap, we examined the prevalence, risk markers, and comorbidity of panic disorder defined using DSM-IV criteria among older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
3
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 33 publications
(56 reference statements)
1
20
3
1
Order By: Relevance
“…[92] Findings from a large nationally representative sample in Canada revealed that among those aged 55 and older (N 5 12,792), psychiatric comorbidity significantly predicted the presence of SOP [22] and PD. [33] In particular, strong associations with PD were observed for MDD and SOP. [33] Data from a large, nationally representative sample of older adults (National Epidemiological Survey on Alcohol and Related Conditions, NESARC; 55 and older) in the United States (N 5 13,420) also observed high comorbidity of MDD for those with SOP (38.5%).…”
Section: Comorbidity and Differential Diagnosismentioning
confidence: 96%
See 4 more Smart Citations
“…[92] Findings from a large nationally representative sample in Canada revealed that among those aged 55 and older (N 5 12,792), psychiatric comorbidity significantly predicted the presence of SOP [22] and PD. [33] In particular, strong associations with PD were observed for MDD and SOP. [33] Data from a large, nationally representative sample of older adults (National Epidemiological Survey on Alcohol and Related Conditions, NESARC; 55 and older) in the United States (N 5 13,420) also observed high comorbidity of MDD for those with SOP (38.5%).…”
Section: Comorbidity and Differential Diagnosismentioning
confidence: 96%
“…[33] In particular, strong associations with PD were observed for MDD and SOP. [33] Data from a large, nationally representative sample of older adults (National Epidemiological Survey on Alcohol and Related Conditions, NESARC; 55 and older) in the United States (N 5 13,420) also observed high comorbidity of MDD for those with SOP (38.5%). [93] In addition, Chou et al [93] found that 35.2% of those who met diagnostic criteria for SOP also met diagnostic criteria for alcohol abuse or dependence.…”
Section: Comorbidity and Differential Diagnosismentioning
confidence: 96%
See 3 more Smart Citations